Strategi Pembelajaran Kurikulum Merdeka Belajar pada Mata Pelajaran Fikih di Kelas X Madrasah Aliyah Miftahussalam Medan - Amanda, Fricilia; Siregar, Bahtiar (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This study aims to determine the strategy of fiqh teachers in the independent learning curriculum learning process in fiqh subjects in class X of Madrasah Aliyah Miftahussalam Medan. (a) The independent learning curriculum emphasizes flexible, contextual learning, and is oriented towards developing students' competencies as a whole. In fiqh subjects, learning strategies focus on strengthening the understanding of fiqh concepts that can be applied in everyday life, as well as developing students' critical thinking skills and character. This study found that the application of project-based learning, discussion, and the use of technology are effective methods in exploring fiqh material. In addition, continuous and competency-based evaluation is also an important aspect in monitoring student development. (b) This study was conducted using a qualitative method, with a field study approach. (c) The results of this study are expected to provide important insights for educators in developing more relevant learning strategies according to the needs of students in facing the challenges of the 21st century.